Analysis of Antiretroviral Drugs (ARV) Logistic Management in the Province of Sumatera Utara (Case Study: Regional Public Hospital Dr. Pirngadi Medan And Public Hospital HKBP Balige): English - Lumbanraja, Linnon Bastian; Nasution, Azizah; Dalimunthe, Aminah (Talenta Publisher, 2021)
Good drug management including planning, procurement, storage, distribution, destruction, recording and reporting is one of the tasks of the North Sumatra Provincial Health Office and HIV Services in the Regency/City. The purpose of this study was to analyze the drug management of the Antiretroviral program drugs in 2019 and 2020 at the Pharmacy Warehouse of the Health Office of North Sumatra Province, the Pharmacy Installation of Pirngadi Hospital Medan, and Pharmacy Installation at HKBP Balige Hospital. The research was conducted in January-April 2021. This research is descriptive with quantitative data obtained retrospectively and concurrently, qualitative data obtained through observation and interviews with informants. The data obtained were analyzed using indicators and compared to standard research results. The results showed in the North Sumatra Provincial Health Office 5 indicators have not met the standards and 9 indicators have met the standards, in Pirngadi Hospital Medan 4 indicators have not met the standards and 8 indicators have met the standards, but have not done the process of planning drug needs, and in HKBP Balige Hospital there are no indicators that meet the standards and do not do the planning of drug needs. The conclusion of this study is drug planning at the North Sumatra Provincial Health Office using the consumption method of the previous period. Pirngadi Hospital Medan and HKBP Balige Hospital did not plan for drug needs. Drug distribution at the North Sumatra Provincial Health Office uses a decentralized system starting in 2020 from the previous centralized system. In Pirngadi Hospital Medan the system is decentralized, while at HKBP Balige Hospital the distribution system is centralized.